Penerapan Digital Web Design Marketing dalam Meningkatkan Strategi Pemasaran UMKM Kuliner Abak Chef The Bastley - Dea Stevy Husna; Maha Rani; Sularno Sularno; Zulfitri Yani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The rapid development of digital technology offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve their marketing strategies through the implementation of digital web design marketing. This study aims to analyze how the utilization of a website designed with a strategic web design approach can support the promotion and sales of products in the culinary MSME Abak Chef The Bastley. The developed website showcases the business profile, menu offerings, delivery services, and promotional content optimized to attract online customers. The research methods include literature study, direct observation, and document analysis related to the MSME’s profile. The results reveal that the presence of a website facilitates easier access to product information, expands marketing reach, and enhances the professional image of the MSME in the eyes of consumers. Therefore, implementing digital web design marketing proves to be an effective strategy for culinary MSMEs to adapt to the digital marketing era and improve business competitiveness. costs.